Implementation of Islamic Character Building Management Between Educators and Student in Improving Spiritual Competence at Namira Tahfizul Qur’an Elementary School - Muchlis Anshori; Zaki Rakhmawan; Nely Nurhayati (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: The Islamic character that is increasingly disappearing in the world of education in Indonesia is becoming more and more uncontrollable, in line with the policies of the holders of national education control in Indonesia which do not make the formation of Islamic character domination that must be fought for and continuously improved. The decline in Islamic character that is not good by the nation's successors occurs in all aspects of life, starting from the way of dressing, speaking and daily behaviour. For this reason, the formation of Islamic character is very important to be instilled, especially in schools by using the management of Islamic character formation that applies to educators as well as students. This study aims to determine the implementation of Islamic character-building management between educators and students at SDIT Tahfizh Qur'an Namira Magelang Regency in improving spiritual competence. using a descriptive method with a qualitative approach. Data collection is done by documentation, observation, and interviews related to the object under study. Then analyzed using descriptive qualitative analysis. The results of this study are (1) planning for character education at SDIT Tahfizh Qur'an is carried out through a meeting at the beginning of the education year involving many parties, including teachers, staff, other employees and also parents (2) implementation of character education at SDIT Tahfizh Qur'an Namira through the integration of character values into subjects, training teachers by inviting experts, adding or improving the curriculum, habituation and exemplary teachers (3) evaluation (assessment) of the management of Islamic character formation at SDIT Tahfizh Qur'an Namira, namely the principal evaluates each predetermined period in each class and students are given an evaluation book when doing activities at home. Keywords: Management, Character Education, Educators, Students